Indonesian Tes and Measurment Instrument for Deaf-Male Students Aged 13-15 Years-15 Tahun - Irawan, Ricko (Journal of Physical Education Health and Sport, 2019)
The main problem of this research is the absence of parameters and evaluation tools on the physical fitness test of deaf students in extraordinary school(SLB). This research method uses a development method with procedural models and indicators used in TKJIT-03 including: (1) speed, (2) endurance of arm and shoulder muscles, (3) abdominal muscle strength, (4) leg muscle explosive power, and (5) heart endurance. Results: 1) 50 m sprint average 11.25 SD 3.50. 2) average push dynamometer 14.71 SD 6.77. 3) average dynamometer pull of 17.37 SD 8,20. 4) lie down sitting 60 seconds on average 18.33 SD 9.65. 5) vertical jumps averaged 33.5 SD 14.99 and 6) average 10.80 SD 4.61. The TKJIT-03 test is ideal for use in physical fitness tests for deaf children as well as evaluating learning fitness subjects in an SLB.